ANALISIS HARGA, CITA RASA, LOKASI, KUALITAS PRODUK, DAN PROMOSI TERHADAP LOYALITAS PELANGGAN DIMEDIASI KEPUTUSAN PEMBELIAN PADA USAHA WAKHID PENTOL - Moh. Arief Zadana Rosyidi; Abid Muhtarom; Muhammad Chusnul Khitam (Jurnal Bina Bangsa Ekonomika, 2023)
The increasing development of UMKM in Indonesia from year to year has the effect of increasingly fierce competition between businesses. One of the businesses that is growing rapidly is the culinary field, because it is felt that the culinary business has more promising prospects. The purpose of this study is to determine the effect of price, taste, location, product quality and promotion on customer loyalty mediated by purchasing decisions. Using a quantitative approach with a sample of 315 respondents, with SEM analysis using the Smart PLS application version 3.0. by testing the outer model, inner model, mediation test and hypothesis testing. The results obtained in the validity test stated that the loading factor was ≥ 0.7 and the AVE value ≥ 0.5 so that it could be declared valid, in the composite reliability test and Cronbach's alpha ≥ 0.7 so it could be declared reliable. The results showed that price (X1) had a positive and significant effect on customer loyalty (Y), price (X1) had a positive and significant effect on purchasing decisions (Z), taste (X2) had a negative and significant effect on customer loyalty, taste taste (X2) has a positive and significant effect on purchasing decisions (Z), location (X3) has a positive and significant effect on customer loyalty (Y), location (X3) has a positive and insignificant effect on purchasing decisions (Z), product quality (X4) ) on customer loyalty (Y) has a negative and significant effect, product quality (X4) on purchasing decisions (Z) has a positive and significant effect, promotion (X5) has a positive and insignificant effect on customer loyalty (Y), promotion (X5) on decisions purchase (Z) has a negative and significant effect and purchase decision (Z) on customer loyalty (Y) has a positive and significant effect